Interkulturelles Marketing: Gegenüberstellung von Erfolgsfaktoren der Kundenansprache in der DACH-Region und Südkorea am Beispiel dekorativer Kosmetik - J. Günther; K. Hartmann; M. Simon; G. Walter (Research Journal for Applied Management (RJAM), 2020)
– This paper investigates whether it is advantageous for the cosmetics industry to address customers in the two target markets DACH region (Germany, Austria, and Switzerland) and South Korea in a differ-entiated way, adapted to the cultural values of the respective target market. For this purpose a survey of 100 inhabitants of the DACH region and 100 South Koreans was conducted. Cultural values and needs, preferences in advertising, the relationship between consumers and companies, and consumer behavior were surveyed using a questionnaire with identical content in German and Korean. It was found that consumers in the respective target markets differ in their reactions to identical advertising messages. Based on the results, a differentiated application is recommended for players in the cos-metics industry. However, companies should always consider the advantages in relation to the costs and resources involved.
Keywords: 650; interkulturelles Marketing; Kulturdimensionen; Marketingstrategie; dekorative Kosmetik; Erfolgsfaktoren; Kundenansprache